Uso da ferramenta ndwi para modelo de análise de disponibilidade de água - Cardia, Luiz Henrique; Martin, André Luis Sotero Salustiano; Fais, Laura Maria Canno Ferreira (International Workshop for Innovation in Safe Drinking Water, 2022)
Environmental problems related to water resources and soil degradation are increasingly frequent, resulting in changes in the hydrological cycle and in the fluvial characteristics of hydrographic basins. The presence of small dams along the hydrographic network can contribute to the guarantee of ecological flow, even in periods of drought. However, the identification and location of these structures is difficult, as they often do not have the proper authorization. Thus, this work aims to evaluate the availability of water in the Piraí River Basin, using the Normalized Difference Water Index (NDWI) tool, based on satellite images. The Ribeirão Piraí sub-basin is located in the region of the Piracicaba-Capivari-Jundiaí River Basin (PCJ), and has accelerated urban growth, which together with the increase in other human activities in recent decades, contributes to a significant change in several natural cycles. From the results, it is observed that the tool proved to be adequate to perform the temporal analysis of the formation of water mirrors (through the sequential analysis of successive satellite images) to understand the regional dynamics, as well as the general water availability of the basin.